Nonlocal Boundary Value Problem for Nonlinear Impulsive qk-Integrodifference Equation - Lihong Zhang; Dumitru Baleanu; Guotao Wang (Abstract and Applied Analysis)
A nonlinear impulsive integrodifference equation within the frame of qk-quantum calculus is investigated by applying using fixed point theorems. The conditions for existence and uniqueness of solutions are obtained.